Quantitative Changes in Selected Soil Health Indices as a Result of Long-Term (23-Year) Cultivation of Winter Wheat in Various Crop Rotations: Case Study for Sandy Soil - Monika Jakubus; Katarzyna Panasiewicz (Agriculture, 2025)
Perennial monoculture crops are perceived as detrimental to soil health. This study examines this assumption with regard to winter wheat cultivated in crop rotations with varying cereal shares (50%, 75%, and 100%) and under different irrigation regimes. The experiments were established in light, sandy soil and conducted as static trials over 23 years (1997–2020). This study aims to assess the quantitative changes in parameters indicative of soil fertility and health. The amounts of total organic carbon (TOC), humic substance carbon (HSC), total nitrogen (TN), and available forms of N, P, K, and Mg (AN, AP, AK, AMg) were measured. It was found that, regardless of the research year, higher levels of TOC, TN, AP, AK, and AMg were recorded in the soil following winter wheat cultivated in a rotation with a 100% share of cereals. The amounts of the above-mentioned parameters were higher by 10–30%. The effect of crop rotation on the quantitative changes in HSC and AN was not statistically significant, although a decrease in their amounts was noted (by 10%). The reduction in HSC content was accompanied by a decline in the quality of these compounds, as indicated by Q4/6 values, which were significantly higher in plots with sprinkling irrigation and under winter wheat cultivated in rotations with a 100% cereal share; this was evident in both 1997 and 2020. Sprinkling irrigation resulted in lower amounts of TOC, TN, HSC, AN, and AK, but higher levels of AP and AMg. The results directly indicate that the long-term cultivation of winter wheat in rotations with a 100% cereal share in light soils leads to quantitative changes in soil health indices. These changes are generally positive, favorably affecting the health of light soils, in contrast to the effects observed with irrigation.